2021
DOI: 10.3390/microorganisms9020257
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization and Genetic Diversity of Haplogroup E Human Lice in Guinea, West Africa

Abstract: Pediculus humanus capitis, the head louse, is an obligate blood-sucking ectoparasite that occurs in six divergent mitochondrial clades (A, D, B, F, C and E). Several studies reported the presence of different pathogenic agents in head lice specimens collected worldwide. These findings suggest that head louse could be a dangerous vector and a serious public health problem. Herein, we aimed to study the mitochondrial genetic diversity, the PHUM540560 gene polymorphisms profile of head lice collected in Guinea, a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 55 publications
0
11
0
1
Order By: Relevance
“…Co-infestations of different haplotypes as well as clades in one person were described. Therefore, interbreeding may be responsible for such connections [ 27 , 34 , 35 ]. For the collected head lice in our study, the phylogenetic analysis revealed two distinct clades of head lice; clade A and C ( Fig 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…Co-infestations of different haplotypes as well as clades in one person were described. Therefore, interbreeding may be responsible for such connections [ 27 , 34 , 35 ]. For the collected head lice in our study, the phylogenetic analysis revealed two distinct clades of head lice; clade A and C ( Fig 1 ).…”
Section: Resultsmentioning
confidence: 99%
“…To assess clade diversity in human lice, the obtained cytb sequences were combined and compared with worldwide cytb data previously reported and deposited in the GenBank database [8,22]. Alignments were performed using MEGA7.0.26 software and a Maximum-Likelihood (ML) tree was constructed using the Kimura2-parameter model under 1,000 bootstrap replicates [23].…”
Section: Data Analysis 241 Phylogenetic Analysismentioning
confidence: 99%
“…In addition, the DNA of several pathogenic bacteria have been reported in head lice, including B. quintana, C. burnetii, B. recurrentis, Y. pestis, R. aeschlimannii, Anaplasma, Ehrlichia and Acinetobacter spp. (Piarroux et al, 2013;Drali et al, 2015;Amanzougaghene et al, 2016;Amanzougaghene et al, 2017;Candy et al, 2018;Boumbanda Koyo et al, 2019;Amanzougaghene et al, 2020b;Boumbanda-Koyo et al, 2020;Hammoud et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…aeschlimannii, Anaplasma , Ehrlichia and Acinetobacter spp. ( Piarroux et al, 2013 ; Drali et al, 2015 ; Amanzougaghene et al, 2016 ; Amanzougaghene et al, 2017 ; Candy et al, 2018 ; Boumbanda Koyo et al, 2019 ; Amanzougaghene et al, 2020b ; Boumbanda-Koyo et al, 2020 ; Hammoud et al, 2021 ).…”
Section: Introductionunclassified